Gas supply security model to EU consumers - Babenko, Vitalina (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2020)
Recently, the problem of choosing methods of establishing transit tariffs for natural gas transportation services to consumers of EU countries and finding ways to adapt them to the conditions of an international gas transportation consortium (IGTC) has become even more significant. The subject of the article is the problems of Ukrainian gas supply security to consumers of the EU countries using international economic and legal mechanisms. The purpose of the article is to develop a methodology for regulating transit Ukrainian-European gas supplies by creating IGTC "Ukraine-EU" to increase competition and establish an acceptable and mutually beneficial gas price for the end European consumer and for the gas transportation system itself. Research objectives: substantiating the solution of the problems associated with gas transit with the help of economic policy instruments; developing a method of forming IGTC "Ukraine-EU". General scientific research methods were used: synthesis, analysis, systematic approach, statistical analysis of international tariff setting practice application to resolve controversial issues related to the transit of natural gas. Main results and their scientific novelty. Based on the forecast of growth in demand for natural gas in the EU, the author shows the effectiveness of forming IGTC "Ukraine-EU" to ensure reliable gas transit through the territory of Ukraine. A unified mechanism for transit gas supplies through the gas pipeline system of Ukraine under the conditions of the functioning of the “Ukraine-EU” consortium has been proposed. Conclusions: using the mechanism for coordinating the interests of individual participants with the proposed methods will significantly raise the level of security of gas supplies to consumers in the EU countries - both within the framework of the proposed gas transportation consortium with European countries, and for other gas transportation projects.